Review paperCauses, symptoms and prevention of food allergy - Żukiewicz-Sobczak, Wioletta Agnieszka; Wróblewska, Paula; Adamczuk, Piotr; Kopczyński, Przemysław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Currently, food allergy is considered to be one of the diseases of civilization, which occurs as a result of the changing conditions of life and environmental changes (e.g. increased popularity of cesarean delivery, excessive hygienic regime during the neonatal-infantile period). Based on medical statistics, it can be concluded that this problem will be intensified. Consumption of food is one of the main activities in human life. What and how one eats affects our health. Meals eaten regularly provide the components necessary for the energy metabolism. Multicultural society, travel, and new trends affect the diversity of food consumed. The mechanism of food allergy reaction covers all 4 types of the immune response of the classical division of Gell and Coombs. The percentage of the immune response was assessed by Chandra as follows: type I – 48%, type II – 6%, type III – 10%, and type IV – 18%. The article presents the risk factors for food allergy, most common symptoms, preventive measures and characteristics of food products that are potential allergens.